1988
DOI: 10.2307/249214
|View full text |Cite
|
Sign up to set email alerts
|

Using a GDSS to Facilitate Group Consensus: Some Intended and Unintended Consequences

Abstract: A cumulative body of experimental research is emerging that examines the ability of computer technology to support the processes and outcomes of small group meetings. For the most part the group decision support system effort has been concerned with demonstrating the usefulness of the technology in planning and decisionmaking situations where the quality of the meeting's outcomes can be objectively assessed. In many decision situations, however, there is no objective measure of decision quality available. Rath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
169
0
2

Year Published

1999
1999
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 402 publications
(171 citation statements)
references
References 19 publications
(41 reference statements)
0
169
0
2
Order By: Relevance
“…For the idea generation task, we proposed brainstorming (Watson et al 1988). A group uses brainstorming to indicate the verbal generation of ideas.…”
Section: Methodsmentioning
confidence: 99%
“…For the idea generation task, we proposed brainstorming (Watson et al 1988). A group uses brainstorming to indicate the verbal generation of ideas.…”
Section: Methodsmentioning
confidence: 99%
“…Where feasible, items were adapted from items used in previous studies (e.g., [27,29,30,[32][33][34][35][36]). All items are presented in the appendix.…”
Section: Dependent Variablesmentioning
confidence: 99%
“…Some experiments have used a more sensitive measure based on fuzzy set theory (Sambamurthy & Chin, 1994;Tan, Wei, & Krishnamurthy, 1991;Watson et al, 1988, Sep), but this only works with interval data, not nominal data such as limited-choice tasks usually produce, and requires data in the form of voting probabilities (Tan, Teo, & Wei, 1995). The measure used in this study can be applied to interval, ordinal and nominal data.…”
Section: Agreementmentioning
confidence: 99%
“…The suggestion that computers support task rather than social interaction has a long research history (Hiltz, Johnson, & Turoff, 1986;Ho & Raman, 1991;Siegel, Dubrovsky, Kiesler, & McGuire, 1986). However there is an equally long history reporting no difference between computer and FTF groups in generating agreement (Watson, DeSanctis, & Poole, 1988, Sep), and in a recent review, 58 of the 67 studies measuring consensus showed no main effect for computer-mediated by FTF (Fjermestad & Hiltz, 1999a). And some studies report computer-mediated groups generate more consensus than FTF interaction (Lea & Spears, 1991;Postmes & Spears, 1998).…”
mentioning
confidence: 99%